Woman as an executive member of society - Thompson, Sarah Pauline (My University, 1903)
Introduction: Ever since the history of the world began it has been woman’s mission to make and keep the home, to prepare women for future home-keeping, to train men for battle and, later in the stage of civilization, for statesmanship. Drummond says that development of the human race may by learned by a study of the “evolution of mothers.” The innate mother love saw the need for protection of child life from the elements and, as a result, a primitive shelter was secured, first beneath a projecting rock, followed by hollowing out of the mountain sides and the construction of caves and hovels. After general shelter was secured it was necessary for individuals to be protected, exposure sometimes being necessary in times of storm. This condition suggested personal covering in the shape of leaves, or skins of animals. Thus each step in civilization is the direct outgrowth of the mother love which exhibits itself in surrounding the child that it may grow to manhood or womanhood. The growth of woman’s education has been slow. While men were trained in war and protection, the daughters were instructed in the care of the home and all its allied industries. At the same time there was inculcated the idea that marriage was the ultimate end to be gained. In order to afford entertainment women were instructed in such accomplishments as music and dancing. With this, as an entering wedge, commenced the education of women; advancing by stages until now women may secure an education equal and in the same classes with men. With the removal of many of the home industries to the manufacturing establishments, time has been given to pursue more advanced work.
Citation: Thompson, Sarah Pauline. Woman as an executive member of society. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Wordsworth; Nature Poet; Early Influences; Theses